Haze episodes at Syowa Station, Antarctica - Keiichiro Hara; Kazuo Osada; Masanori Yabuki; Gen Hashida; Takashi Yamanouchi; Masahiko Hayashi; Masataka Shiobara; Chiharu Nishita-Hara; Makoto Wada (National Institute of Polar Research, 2010)
During our aerosol measurement program at Syowa Station, Antarctica in 2004-2007, some low visibility (haze) phenomena were observed under conditions with weak wind and without drifting snow and fog in winter-spring. In the "Antarctic haze" phenomenon, the number concentration of aerosol particles and black carbon concentration increased by one-two orders higher relative to background conditions at Syowa Station, while surface O_3 concentration simultaneously dropped especially after polar sunrise. Major aerosol constituents in the haze phenomenon were sea-salts (e.g., Na^+ and Cl^-). From the trajectory analysis and NAAPS model, the plumes from biomass burning in South America and southern Africa were transported to Syowa Station, Antarctic coast, during eastward (occasionally westward) approach of cyclones in the Southern Ocean. Thus, poleward flow of the plume from mid-latitudes and injection of sea-salt particles during the transport may lead to the Antarctic haze phenomenon at Syowa Station. The difference of O_3 concentration between the background and the haze conditions tended to be larger in spring (polar sunrise) relative to that in winter. Because enhancement of sea-salt particles can play an important role as an additional source of reactive halogen species, the haze episodes might make a significant contribution to surface O_3 depletion during the polar sunrise on the Antarctic coast.